2018
DOI: 10.3390/bioengineering5030074
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Hemodynamic Conditions Associated with Mechanical Heart Valve Leaflet Immobility

Abstract: Artificial heart valves may dysfunction, leading to thrombus and/or pannus formations. Computational fluid dynamics is a promising tool for improved understanding of heart valve hemodynamics that quantify detailed flow velocities and turbulent stresses to complement Doppler measurements. This combined information can assist in choosing optimal prosthesis for individual patients, aiding in the development of improved valve designs, and illuminating subtle changes to help guide more timely early intervention of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 54 publications
2
18
0
1
Order By: Relevance
“…Their findings are in a good agreement with our experimental results. In the case of BMHV dysfunction, only few studies are reported in the literature and their results in terms velocity profiles and AVSS are in a good qualitative agreement with our experimental findings. A thorough quantitative comparison is still difficult because the reported numerical simulations did not include fluid–structure interaction and considered stationary BMHV leaflets.…”
Section: Discussionsupporting
confidence: 90%
“…Their findings are in a good agreement with our experimental results. In the case of BMHV dysfunction, only few studies are reported in the literature and their results in terms velocity profiles and AVSS are in a good qualitative agreement with our experimental findings. A thorough quantitative comparison is still difficult because the reported numerical simulations did not include fluid–structure interaction and considered stationary BMHV leaflets.…”
Section: Discussionsupporting
confidence: 90%
“…When hemoglobin is released into the blood stream it lowers the oxygen carrying capacity of the blood and, in levels that are too high, can be toxic to the body. Computational fluid dynamics (CFD) studies to simulate flow through prosthetic heart valves often cite blood damage as a motivation with little attention to predicting hemolysis [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The hematologic consequences of a leaflet that partially opens may be profound. In a computational fluid dynamics study of the effects of mechanical bileaflet valve dysfunction in the aortic position in which one leaflet does not fully open, Khalili et al 13 found that leaflet immobility resulted in flow separation and increased turbulent stress. Turbulent shear forces produce both hemolysis and platelet activation.…”
Section: Hematologic Consequences Of Leaflet Immobilitymentioning
confidence: 99%